2022
DOI: 10.1177/13506501221132110
|View full text |Cite
|
Sign up to set email alerts
|

Frictional analysis on stiffness and damping characteristics of bump foil gas bearings

Abstract: Gas foil bearing has been used in high-speed turbomachinery for its high speed, high adaptability, and eco-friendly. The stability of the rotor bearing system is greatly enhanced due to the flexible foil support structure. In the foil supporting structure, vibration energy of the rotor bearing system can be absorbed by the Coulomb friction dissipation. In order to evaluate the frictional dissipation on bearing performance, a quasi-2-dimensional mechanical model is proposed considering the Coulomb friction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…[𝐾] = ∑[𝐾] 𝑖 𝑖=1 , {𝑓} = ∑{𝑓} 𝑒 𝑖 (5) [𝐾]{∆𝑐} = {𝑓} (6) Equivalent damping was introduced to represent the energy dissipation capacity, as shown in the following [50]:…”
Section: ∂(ρU) ∂Xmentioning
confidence: 99%
See 1 more Smart Citation
“…[𝐾] = ∑[𝐾] 𝑖 𝑖=1 , {𝑓} = ∑{𝑓} 𝑒 𝑖 (5) [𝐾]{∆𝑐} = {𝑓} (6) Equivalent damping was introduced to represent the energy dissipation capacity, as shown in the following [50]:…”
Section: ∂(ρU) ∂Xmentioning
confidence: 99%
“…Equivalent damping was introduced to represent the energy dissipation capacity, as shown in the following [50]:…”
Section: Grid Independence and Model Validationmentioning
confidence: 99%
“…In subsequent studies, many scholars have proposed different ways to introduce Coulomb friction to improve the model and the calculation formula of foil stiffness. [14][15][16][17][18][19] Zhao et al 20 analyzed the friction of bump foil bearings with different structures, and found that in engineering operation of the foil bearings design, friction coefficient and bump height need to be selected properly to obtain optimal stiffness and damping characteristics of the foil bearings. The research object of these improved models is the bump foil, while ignoring the influence of the flat foil.…”
Section: Introductionmentioning
confidence: 99%
“…Gas foil bearings, known for their structural simplicity, cost-effectiveness, environmental friendliness, and high-speed stability, 1,2 have gained significant traction in the realm of high-speed turbo machinery, including micro gas turbines, turbo expanders, and centrifugal compressors. 36 On the one hand, micro gas turbines operate under extreme temperature conditions, with operating temperatures ranging from 600 to 1000 °C.…”
Section: Introductionmentioning
confidence: 99%